Knowing and Being Known: Parents' Experiences with Rural Schools - Jerry McClelland (Journal of Research in Rural Education, 1997)
Members ofrural communities tend to be well acquainted with each other. This phenomenological study examines what it is like for parents to know and be known by others in rural schools. The main themes characterizing their experiences are that parents know the teachers and principal, it is common knowledge whenever a child has a problem at school, and what happens at school can change relationships.